A modified cognitive information complexity measure of software. - Kushwaha, Dharmender Singh
Most discipline of science have their own method of investigation built on foundation that is empirical and verifiable. Cognitive Informatics is no different. Cognitive Informatics is a field that studies internal information processing mechanism of the human brain and its application in software coding and computing. This paper attempts to empirically demonstrate the amount of information contained in software and develops a concept of cognitive information complexity measure based on the information contained in the software. It is found that software with higher cognitive information complexity measure has more information units contained in it. Therefore cognitive information complexity measure can be used to understand the cognitive information complexity and the information coding efficiency of the software.
Keywords: Information systems; Models and principles; Systems and information theory; Software; Software engineering; Metrics; Complexity measures; Theory of computation; Computation by abstract devices; Complexity measures and classes; Computing methodologies; Artificial intelligence; Cognitive simulation; Measurement; Theory; Cognitive informatics; Cognitive information complexity unit; Complexity information complexity; Information coding efficiency; Information unit; Weighted information count